Strategi Peningkatan Minat Perusahaan Beriklan di Garbarata: Studi Kasus di Bandar Udara Internasional Minangkabau Padang - Novan Muhammad Saofi Arkaan; Rafli Aditya Rahman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze strategies that can increase companies' interest in utilizing advertising media at Minangkabau International Airport's jet bridges, Padang. The jet bridge is a strategic area with significant potential as a promotional medium due to the intensity of direct interaction with airline passengers. However, its utilization has not been optimal. This study used a qualitative descriptive approach with data collection methods consisting of in-depth interviews with airport management and advertising companies, observations of advertising media conditions at the location, and documentation studies related to policies and previous marketing data. The results showed that two main obstacles in attracting advertisers were the lack of information provided to potential clients and the high cost of advertising. Many companies were unaware of the strategic potential of advertising media at the jet bridges or the pricing schemes offered. Therefore, strategies identified as effective included increasing digital promotion through social media and the airport's official website, developing a more flexible pricing scheme according to market segmentation, and strengthening collaboration with local stakeholders such as local governments and business associations. The implications of this study emphasize the importance of professional and adaptive advertising media management. Optimizing advertising on boarding bridges not only has the potential to increase non-aeronautical revenue for the airport, but can also strengthen the region's image as a dynamic destination and support local economic growth.